Graphene controlled Brewster angle device for ultra broadband terahertz modulation - Zefeng Chen (Nature Portfolio, 2018)
Low-dimensional materials show promise for applications in imaging, spectroscopy and ultra-broadband communications. Here, the authors report an effect of Brewster angle control at graphene-quartz interface for applications in terahertz modulation over a broadband range from 0.5 to 1.6 THz.